Binocular facilitation in light‐mediated melatonin suppression?. Issue 4 (22nd August 2019) - Spitschan, Manuel; Cajochen, Christian
Abstract: In humans, the production of melatonin is suppressed by light exposure. This effect is mediated by a retinal pathway involving the melanopsin‐containing intrinsincally photosensitive retinal ganglion cells (ipRGCs), which exhibit maximum sensitivity to short‐wavelength light. Here, based on extant and published data,  we examine how signals from the two eyes are integrated in driving the suppression of melatonin by light. We find that melatonin suppression by light exposure to two eyes corresponds to a sensitivity shift by about 1.2 log units (factor ~17.4).